Studi Fenomenologi tentang Penguatan Digital Citizenship Berbasis Literasi Digital dalam Pembelajaran Pendidikan Pancasila di Sekolah Dasar - Eka Dayani Yulianti; Deni Zein Tarsidi; Sukarno Sukarno Sukarno (Universitas Sebelas Maret, 2026)
This study is motivated by the high internet penetration in Indonesia, reaching approximately 80.66% of the population in 2025, while cases of cyberbullying among children continue to rise to an average of 40 cases per month, making the strengthening of digital citizenship from elementary school age an urgent matter. This study aims to analyze digital information access, digital communication, and digital ethics in Pancasila Education learning as a means of strengthening digital citizenship in elementary schools. The study employed a qualitative phenomenological approach with nine teachers and eighteen students from three elementary schools, namely SD Aisyiyah Unggulan Gemolong, SD Kristen Manahan, and SD Negeri Mojo Surakarta, as participants. Data were collected through in-depth interviews, direct observation, and documentation studies, then analyzed using Colaizzi's seven-step method and validated through source and technique triangulation. The results show that digital information access occurred through a teacher-mediated access pattern with varying levels of critical literacy quality across schools, digital communication was formed through a triangular school–parent–student ecosystem via WhatsApp groups, and digital ethics was organically integrated with Pancasila values without formal coordination among schools. This study implies that integrating digital citizenship does not require a new subject, but can instead be carried out contextually by linking digital ethics to existing Pancasila values in learning, so that students become not only technically competent but also of good character.